Analysis of the Localization of Fluorescent PpROP1 and PpROP-GEF4 Fusion Proteins in Moss Protonemata Based on Genomic “Knock-In” and Estradiol-Titratable Expression - le Bail, Aude; Schulmeister, Sylwia; Perroud, Pierre-François; Ntefidou, Maria; Rensing, Stefan A.; Kost, Benedikt (Frontiers in Plant Science, 2019)
Tip growth of pollen tubes, root hairs, and apical cells of moss protonemata is controlled by ROP (Rho of plants) GTPases, which were shown to accumulate at the apical plasma membrane of these cells. However, most ROP localization patterns reported in the literature are based on fluorescent protein tagging and need to be interpreted with caution, as ROP fusion proteins were generally overexpressed at undefined levels, in many cases without assessing effects on tip growth. ROP-GEFs, important regulators of ROP activity, were also described to accumulate at the apical plasma membrane during tip growth. However, to date only the localization of fluorescent ROP-GEF fusion proteins strongly overexpressed using highly active promoters have been investigated. Here, the intracellular distributions of fluorescent PpROP1 and PpROP-GEF4 fusion proteins expressed at essentially endogenous levels in apical cells of Physcomitrella patens “knock-in” protonemata were analyzed. Whereas PpROP-GEF4 was found to associate with a small apical plasma membrane domain, PpROP1 expression was below the detection limit. Estradiol-titratable expression of a fluorescent PpROP1 fusion protein at the lowest detectable level, at which plant development was only marginally affected, was therefore employed to show that PpROP1 also accumulates at the apical plasma membrane, although within a substantially larger domain. Interestingly, RNA-Seq data indicated that the majority of all genes active in protonemata are expressed at lower levels than PpROP1, suggesting that estradiol-titratable expression may represent an important alternative to “knock-in” based analysis of the intracellular distribution of fluorescent fusion proteins in protonemal cells.<br
Keywords: XFP tagging; genomic knock-in; estradiol-inducible expression; Physcomitrella patens; ROP signaling

Physcomitrium patens PpRIC, an ancestral CRIB-domain ROP effector, inhibits auxin-induced differentiation of apical initial cells - Ntefidou, Maria; Eklund, D. Magnus; le Bail, Aude; Schulmeister, Sylwia; Scherbel, Franziska; Brandl, Lisa; Dörfler, Wolfgang; Eichstädt, Chantal; Bannmüller, Anna; Ljung, Karin; Kost, Benedikt (Cell Reports, 2023)
RHO guanosine triphosphatases are important eukaryotic regulators of cell differentiation and behavior. Plant ROP (RHO of plant) family members activate specific, incompletely characterized downstream signaling. The structurally simple land plant Physcomitrium patens is missing homologs of key animal and flowering plant RHO effectors but contains a single CRIB (CDC42/RAC interactive binding)-domain-containing RIC (ROP-interacting CRIB-containing) protein (PpRIC). Protonemal P. patens filaments elongate based on regular division and PpROP-dependent tip growth of apical initial cells, which upon stimulation by the hormone auxin differentiate caulonemal characteristics. PpRIC interacts with active PpROP1, co-localizes with this protein at the plasma membrane at the tip of apical initial cells, and accumulates in the nucleus. Remarkably, PpRIC is not required for tip growth but is targeted to the nucleus to block caulonema differentiation downstream of auxin-controlled gene expression. These observations establish functions of PpRIC in mediating crosstalk between ROP and auxin signaling, which contributes to the maintenance of apical initial cell identity.
CRIS-Team Scopus Importer:2023-02-24
Keywords: auxin; cell differentiation; CP: Developmental biology; CP: Plants; CRIB domain; initial cells; land plant evolution; nuclear targeting; Physcomitrium patens; RHO/ROP effectors; RHO/ROP GTPases; tip growth

Plasma membrane and cytoplasmic compartmentalization: A dynamic structural framework required for pollen tube tip growth - Fritz, Carolin; Reimann, Theresa; Adler, Jeremy; Knab, Johanna; Schulmeister, Sylwia; Kriechbaum, Choy; Müller, Sabine; Parmryd, Ingela; Kost, Benedikt (Plant Physiology, 2024)
Rapid, unidirectional pollen tube tip growth is essential for fertilization and widely employed as a model of polar cell expansion, a process crucial for plant morphogenesis. Different proteins and lipids with key functions in the control of polar cell expansion are associated with distinct domains of the plasma membrane (PM) at the pollen tube tip. These domains need to be dynamically maintained during tip growth, which depends on massive secretory and endocytic membrane trafficking. Very little is currently known about the molecular and cellular mechanisms responsible for the compartmentalization of the pollen tube PM. To provide a reliable structural framework for the further characterization of these mechanisms, an integrated quantitative map was compiled of the relative positions in normally growing Nicotiana tabacum (tobacco) pollen tubes of PM domains (i) enriched in key signaling proteins or lipids, (ii) displaying high membrane order, or (iii) in contact with cytoplasmic structures playing important roles in apical membrane trafficking. Previously identified secretory and endocytic PM domains were also included in this map. Internalization of regulatory proteins or lipids associated with PM regions overlapping with the lateral endocytic domain was assessed based on brefeldin A treatment. These analyses revealed remarkable aspects of the structural organization of tobacco pollen tube tips, which (i) enhance our understanding of cellular and regulatory processes underlying tip growth and (ii) highlight important areas of future research.
Created from Fastlane, Scopus look-up

SUCROSE TRANSPORTER 5 supplies Arabidopsis embryos with biotin and affects triacylglycerol accumulation - Pommerrenig, Benjamin; Popko, Jennifer; Heilmann, Martin; Schulmeister, Sylwia; Dietel, Katharina; Schmitt, Bianca; Stadler, Ruth; Feussner, Ivo; Sauer, Norbert (Plant Journal, 2013)
The Arabidopsis SUC5 protein represents a classical sucrose/H(+) symporter. Functional analyses previously revealed that SUC5 also transports biotin, an essential co-factor for fatty acid synthesis. However, evidence for a dual role in transport of the structurally unrelated compounds sucrose and biotin in plants was lacking. Here we show that SUC5 localizes to the plasma membrane, and that the SUC5 gene is expressed in developing embryos, confirming the role of the SUC5 protein as substrate carrier across apoplastic barriers in seeds. We show that transport of biotin but not of sucrose across these barriers is impaired in suc5 mutant embryos. In addition, we show that SUC5 is essential for the delivery of biotin into the embryo of biotin biosynthesis-defective mutants (bio1 and bio2). We compared embryo and seedling development as well as triacylglycerol accumulation and fatty acid composition in seeds of single mutants (suc5, bio1 or bio2), double mutants (suc5 bio1 and suc5 bio2) and wild-type plants. Although suc5 mutants were like the wild-type, bio1 and bio2 mutants showed developmental defects and reduced triacylglycerol contents. In suc5 bio1 and suc5 bio2 double mutants, developmental defects were severely increased and the triacylglycerol content was reduced to a greater extent in comparison to the single mutants. Supplementation with externally applied biotin helped to reduce symptoms in both single and double mutants, but the efficacy of supplementation was significantly lower in double than in single mutants, showing that transport of biotin into the embryo is lower in the absence of SUC5.